Penerapan Konsep Arsitektur Islam Dalam Desain Masjid Islamic Center Di Kabupaten Bantaeng - Muhammad Chaidar Febriansyah; Firdaus, Mufli; Amin, Burhanuddin (TIMPALAJA : Architecture Student Journals, 2022)
Masjid is a holy place that is used by Muslims to carry out worship activities and the center of other Islamic activities. The Islamic Center is basically a masjid or worship facility in which it is not limited to worship activities but also includes a variety of other Muslim activities such as educational, social, health, economic, and da'wah centers for the spread of Islam, So that we often hear and see a masjid called the Masjid Islamic Center. The Bantaeng Regency Government has a vision to create a prosperous Bantaeng community that is physically and mentally oriented towards progress, justice, sustainability, and excellence based on religion and local culture. To realize this, we need a forum for Islamic activities that can become the center of Islamic activities in Bantaeng Regency and accommodate the various needs of the Bantaeng community, namely the Islamic Center. The design of the masjid Islamic Center in Bantaeng Regency uses an Islamic architectural approach that is in harmony with the function of the building based on basic Islamic principles, as contained in the Qur'an and Al-Hadith. Then it is poured in the form of architectural design in accordance with the discipline of architecture which is expected to be able to foster public interest and enthusiasm in carrying out Islamic activities, especially for the Muslim community in Bantaeng Regency.